Synergistic effect of proteinuria on dipstick hematuria-related decline in kidney function: The Japan Specific Health Checkups (J-SHC) Study - Tasaki, Hikari; Eriguchi, Masahiro; Yoshida, Hisako; Uemura, Takayuki; Fukata, Fumihiro; Nishimoto, Masatoshi; Kosugi, Takaaki; Matsui, Masaru; Samejima, Ken-ichi; Iseki, Kunitoshi; Asahi, Koichi; Yamagata, Kunihiro; et al. (Clinical and Experimental Nephrology, 2023)
Background The effect of isolated hematuria without proteinuria on kidney function decline, and the modification by the severity of proteinuria in general population are not fully elucidated. Methods Participants were included in the Japan Specific Health Checkups Study between 2008 and 2014. The exposure of interest was the frequency of dipstick hematuria during the observation. In each proteinuria frequency category (non-, occasional, persistent), hematuria-related decline in the eGFR rate was examined by analysis of covariance (ANCOVA). eGFR decline trajectories were also assessed using mixed-effects models. Results Among the 552,951 participants, 146,753 (26.5%) had hematuria, and 56,021 (10.1%) and 8,061 (1.5%) had occasional and persistent proteinuria, respectively. During the median follow-up of 3.0 years, annual change in eGFR decline in participants with hematuria was significantly faster than in those without hematuria (mean [95% confidence interval]: − 0.95 [− 0.98 to − 0.92] vs − 0.86 [− 0.87 to − 0.84] mL/min/1.73 m2/year; P < 0.001). In ANCOVA, the hematuria-related annual eGFR decline rate increased as proteinuria frequency categories increased (differences in annual eGFR decline rate between participants with and without hematuria: 0.08 [0.06 to 0.09] in participants with non-proteinuria category, 0.17 [0.15 to 0.18] in occasional proteinuria category, and 0.68 [0.65 to 0.71] mL/min/1.73 m 2 /year in persistent proteinuria category; P for interaction < 0.001). Similar results were obtained by the linear mixed-effect model. Conclusions Proteinuria has a synergistic effect on dipstick hematuria-related decline in kidney function. Among the general population without proteinuria throughout the observational period, the “isolated hematuria”-related eGFR decline was statistically significant but the difference was small.